نحو تبني آليات بديلة لتمويل التنمية المحلية: الوقف والزكاة – الجزائر انموذجا - بن علال (م) بن رحو, سهام (Revue jurisprudence, 2019)
Development is a requirement for all peoples aspiring to a better future, Strives to achieve advanced and competent authorities that are distributed among different sectors and a levels through different and integrated programs and policies, where the coordination in the crystallization and output to the reality of the efforts of individuals and competent interest search according to its competence. Therefore, the availability of financial development resources is one of the most important factors in promoting economic development on its national or local side, funding is the first challenge to the achievement of various development programs and also one of the key elements and pillars of the success or failure of development program. Studies found that local development is in constant need of funding sources in order to achieve its objectives as efficiently as possible, thus increasing local development rates. Zakat and Waqf are one of the best strategic alternatives sources to fundthe local development process.